Thermoneutrality Alters Gastrointestinal Antigen Passage Patterning and Predisposes to Oral Antigen Sensitization in Mice - Noah, Taeko K.; Lee, Jee-Boong; Brown, Christopher A.; Yamani, Amnah; Tomar, Sunil; Ganesan, Varsha; Newberry, Rodney D.; Huffnagle, Gary B.; Divanovic, Senad; Hogan, Simon P. (Frontiers in Immunology, 2021)
Food allergy is an emerging epidemic, and the underlying mechanisms are not well defined partly due to the lack of robust adjuvant free experimental models of dietary antigen sensitization. As housing mice at thermoneutrality (Tn) - the temperature of metabolic homeostasis (26–30°C) – has been shown to improve modeling various human diseases involved in inflammation, we tested the impact of Tn housing on an experimental model of food sensitization. Here we demonstrate that WT BALB/c mice housed under standard temperature (18–20°C, Ts) conditions translocated the luminal antigens in the small intestine (SI) across the epithelium via goblet cell antigen passages (GAPs). In contrast, food allergy sensitive Il4raF709 mice housed under standard temperature conditions translocated the luminal antigens in the SI across the epithelium via secretory antigen passages (SAPs). Activation of SI antigen passages and the oral challenge of Il4raF709 mice with egg allergens at standard temperature predisposed Il4raF709 mice to develop an anaphylactic reaction. Housing Il4raF709 mice at Tn altered systemic type 2 cytokine, IL-4, and the landscape of SI antigen passage patterning (villus and crypt involvement). Activation of SI antigen passages and the oral challenge of Il4raF709 mice with dietary allergens in Tn conditions led to the robust induction of egg-specific IgE and development of food-induced mast cell activation and hypovolemic shock. Similarly, Tn housing of WT BALB/c mice altered the cellular patterning of SI antigen passage (GAPs to SAPs). Activation of SI antigen passages and the oral challenge of WT BALB/c mice with egg led to systemic reactivity to egg allergens and mast cell activation. Together these data demonstrate that Tn housing alters antigen passage cellular patterning and landscape, and concurrent oral exposure of egg antigens and SAP activation is sufficient to induce oral antigen sensitization.